Effect of Regular Aerobic Exercise on Cognitive Function, Depression Level and Regulative Role of Neurotrophic Factor: A Prospective Cohort Study in the Young and the Middle-Aged Sample - Kong L; Miu L; Yao W; Shi Z (Dove Medical Press, 2024)
Lingming Kong,1,* Liqin Miu,2,* Wenwei Yao,2 Zhiyuan Shi3 1Mental Health Research Center, No. 904th Hospital, Changzhou, Jiangsu, 213003, People's Republic of China; 2Psychiatry Department, the 2nd People's Hospital of Jintan District, Changzhou, Jiangsu, 213200, People's Republic of China; 3College of Clinical Medicine, Yangzhou University, Yangzhou, Jiangsu, 225009, People's Republic of China*These authors contributed equally to this workCorrespondence: Lingming Kong, Mental Health Research Center, North Peace Road 55, No. 904th Hospital, Changzhou, Jiangsu, 213003, People's Republic of China, Email lingmk123@163.comPurpose: Mild cognitive impairment (MCI) and depressive disorder (DD), which are associated with unhealthy lifestyles, are prevalent worldwide. This study aimed to investigate the effects of regular aerobic exercise on cognitive function, depression, and the regulatory role of neurotrophic growth factors for providing scientific basis in preventing MCI and DD in healthy individuals.Patients and Methods: Eighty members of the fitness center and 80 community residents were recruited, who were administered by the Repeatable Battery for the Assessment of Neuropsychological Status (RBANS) and the Patient Health Questionnaire (PHQ-9). Brain-derived neurotrophic factor (BDNF) and glial cell-line-derived neurotrophic factor (GDNF) in the peripheral blood were detected by enzyme-linked immunosorbent assay (ELISA).Results: The RBANS and other factor scores, except for visuospatial abilities, were higher and PHQ-9 scores were lower in the study group than in the control group. The concentrations of BDNF and GDNF in the study group were higher than those in the control group. RBANS and its factor scores positively and PHQ-9 negatively correlated with BDNF and GDNF levels. Finally, multiple regression analysis showed that BDNF, as a predictor of RBANS, could explain 59.90% of its variance and that GDNF was a predictor of PHQ-9 could explain 12.30% of the variance.Conclusion: Regular aerobic exercise can improve cognitive function and depressive symptoms by increasing the BDNF and GDNF levels.Keywords: cognitive impairment, depression level, brain derived neurotrophic factor, glial cell line-derived neurotrophic factor, aerobic exercise